Massive transfusion and the response to prehospital plasma: It is all in how you define it. Issue 1 (July 2020) - Sim, Edward S.; Guyette, Frank X.; Brown, Joshua B.; Daley, Brian J.; Miller, Richard S.; Harbrecht, Brian G.; Claridge, Jeffrey A.; Phelan, Herb A.; Neal, Matthew D.; Forsythe, Raquel; Zuckerbraun, Brian S.; Sperry, Jason L.
Abstract : BACKGROUND: A recent analysis derived from the Prehospital Air Medical Plasma trial data set demonstrated no significant independent plasma survival benefit in those who required massive transfusion (≥10 units of red cells in 24 hours). The definition of massive transfusion has evolved over time to minimize bias and predict those at highest risk of death. We sought to characterize the definition of massive transfusion, their associated mortality risks and the survival benefit associated with prehospital plasma. METHODS: A secondary analysis was performed using data from a recent prehospital plasma trial. Patients transferred directly from the scene were characterized. We defined historic massive transfusion using ≥10 units red cells in 24 hours and critical administration threshold (CAT) as ≥3 units per hour in the first hour (CAT1hr) or in any of the first 4 hours (CAT4hr) from arrival. The primary outcome was 30-day mortality. Kaplan-Meier analysis and Cox hazard regression were used to characterize the survival benefit of prehospital plasma. RESULTS: There were a total of 390 enrolled patients who were transferred from the scene and represent the study cohort. Overall, 126 patients were positive for the CAT1hr metric, 183 patients were positive for the CAT4hr metric and 84 patients were positive for historic massive transfusion metric. The overall study mortality rate for those patients who met each transfusion definition was 13.1%, 17.4% and 10.0%, respectively. The CAT4hr metric had the lowest potential for survival bias. Kaplan-Meier survival analysis demonstrated a prehospital plasma survival benefit in the patients who were CAT4hr positive. CONCLUSION: The current analysis demonstrates the superior utility of the CAT4hr definition with optimization of survival bias while conserving mortality risk prediction. This transfusion definition was associated with a prehospital plasma survival benefit and may be the most appropriate definition of massive transfusion for pragmatic studies which focus on hemorrhagic shock. LEVEL OF EVIDENCE: Epidemiologic, Level II